Key Subordinate Executive Governance, CEO Overconfidence, and Accounting Conservatism: From the Perspective of Sustainable Development - Wu, Fan; Kuang, Xuewen (Frontiers in Psychology, 2022)
Key subordinate executive play the role of connecting superior and subordinate within the top management team (TMT). Based on the heterogeneity of TMT preference, this paper takes the data of Chinese A-share listed companies from 2010 to 2019 as a sample to examine whether key subordinate executive governance can affect the short-sighted behavior of CEO. The empirical result shows that there is a positive relationship between key subordinate executive governance and accounting conservatism, and CEO overconfidence can positively moderate the relationship. The study also shows that there is a significant positive relationship between key subordinate executive governance and accounting conservatism in private enterprises and enterprises with high market competition, that is, the key subordinate executives of these two types of enterprises can better enhance the conservatism under the stimulation of CEO overconfidence. This study contributes to the literature by examining how key subordinate executive affects the accounting conservatism, and links the prudential attitude of key subordinate executives with the behavioral tendency of CEO overconfidence, which has managerial implications for improving the power balance mechanism of TMT and strengthening the human resource incentive of key subordinate executives.